(untitled) (Revista Apotheke, 2025)
Starting from different conceptions of what constitutes a book, this article explores how the boundaries of these definitions can be destabilised through artistic practices. It discusses the practical and conceptual implications of the publications Entre uma coisa e outra (2024), Preposição (2024), and Problems (2025), which possess ISBNs and are cataloguable as books. Adopting a practice-based theoretical approach, it articulates reflections on issues of place and reading, acknowledging the fluidity of the book concept when created by a publishing artist. It highlights the differences between an artist who publishes and a publishing artist, emphasising the need for mastery over the means and processes involved in editorial production. The article concludes that the works presented expand the panorama of the published object and that publication, as an artistic practice, opens new interpretative possibilities regarding what a book can be.